2016
DOI: 10.1016/j.ijmedinf.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eHealth for patients and informal caregivers confronted with cancer: A meta-review

Abstract: There is evidence for positive effects of eHealth on perceived support, knowledge, and information competence of cancer patients. For effects on other outcomes in cancer patients, findings are mainly inconsistent or lacking. This meta-review did not find relevant reviews focusing on or including the effects of eHealth on informal caregivers, which seems a rather unexplored area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 31 publications
4
122
0
1
Order By: Relevance
“…In accordance with other literature reviews and meta-analyses [41,85], the present review found that family members who used telehealth tools reported an increased perception of social support [58,60,65,67] and less negative appraisal of illness and caregiving [52,54,67], even though the overall effect sizes were small. These findings meet the "Research Recommendations for Improving the Assessment of the Prevalence and Burden of Informal Cancer Caregiving" [86], emphasizing the need to direct attention towards the most vulnerable caregivers of cancer patients, such as those socially isolated, living in rural areas, or with low socioeconomic status.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In accordance with other literature reviews and meta-analyses [41,85], the present review found that family members who used telehealth tools reported an increased perception of social support [58,60,65,67] and less negative appraisal of illness and caregiving [52,54,67], even though the overall effect sizes were small. These findings meet the "Research Recommendations for Improving the Assessment of the Prevalence and Burden of Informal Cancer Caregiving" [86], emphasizing the need to direct attention towards the most vulnerable caregivers of cancer patients, such as those socially isolated, living in rural areas, or with low socioeconomic status.…”
Section: Discussionsupporting
confidence: 90%
“…This variability may be related to the enrolment of individuals in different disease stages, undergoing different treatments, or having different psychological and social characteristics, both for the patient and for the caregiver. In fact, it is known that different aspects of the disease or of the treatment may imply different caregiving burdens [41] as well as different psychological or relational issues [90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to a wide variety of knowledge related to breast cancer and chemotherapy may not relieve the women's anxiety and depression [30]. Still literature has inconsistent findings regarding the effects of eHealth on anxiety and depression for cancer patients [31], which needs to be addressed in the future research.…”
Section: Principal Resultsmentioning
confidence: 99%